2019
DOI: 10.1371/journal.pone.0221498
|View full text |Cite
|
Sign up to set email alerts
|

The effect of overnight consolidation in the perceptual learning of non-native tonal contrasts

Abstract: Sleep-mediated overnight consolidation has been found to facilitate perceptual learning by promoting learners’ generalization across talkers in their perception of novel segmental categories. Lexical tone is characterized by high variability across talkers, and displays dynamic change over time. For this reason, it remains unclear whether a similar effect of overnight consolidation would be found for perceptual learning of novel tonal contrasts. Thus, this study aims to examine whether overnight consolidation … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 80 publications
1
16
0
1
Order By: Relevance
“…Overall, the findings of the current study suggest that individual learners had varying degrees of difficulty learning non-native tones (at least, partially) by virtue of the effect of pitch aptitude on tone consolidation (Fuhrmeister & Myers, 2020;Qin & Zhang, 2019). The findings imply that the early emergence of tonal representation is a dynamic process among individual learners, especially when they face training variability (e.g., the inter-talker variability of tones).…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…Overall, the findings of the current study suggest that individual learners had varying degrees of difficulty learning non-native tones (at least, partially) by virtue of the effect of pitch aptitude on tone consolidation (Fuhrmeister & Myers, 2020;Qin & Zhang, 2019). The findings imply that the early emergence of tonal representation is a dynamic process among individual learners, especially when they face training variability (e.g., the inter-talker variability of tones).…”
Section: Discussionmentioning
confidence: 55%
“…To standardize the data, pitch threshold in semitone was log-transformed and z-normalized prior to the and test (2 levels: ID posttest1 vs. ID posttest2; deviation coding: 0.5, 0.5) were entered as fixed effects, and test was nested within group so that the effect of test is examined within each group. Since the focus of the current study is not the differences among individual level tones (1, 2 and 3), and our previous study (Qin & Zhang, 2019) revealed no effect of tone on overnight consolidation of the level-tonal contrasts, tone is thus not included as a fixed effect in the analysis. Nevertheless, tone was put in the random structure to account for its potential effect on response accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…DÉFICIT PROCÉDURAL ET TROUBLE DÉVELOPPEMENTAL DU LANGAGE 14 Ces dernières années, quelques études ont également mis en évidence l'impact positif des processus de consolidation, notamment ceux en jeu au cours du sommeil, sur les apprentissages langagiers (pour des revues, voir Gómez et al, 2011 ;Schreiner & Rasch, 2017), notamment au niveau des processus d'intégration lexicale (Gaskell & Dumay, 2003) de généralisation de régularités importantes pour l'acquisition du langage (Gómez et al, 2006) ou de la discrimination des sons de la parole (Earle & Myers, 2015 ;Qin & Zhang, 2019).…”
Section: Importance De Considérer La Dynamique Des Apprentissages Et ...unclassified